The Legal Consequences of Goods Returns on Business Entities under the Cash on Delivery Payment System (Faculty of Law, Universitas Pattimura, 2025)
Introduction: E-commerce is a part of e-business that focuses on online buying and selling transactions carried out through electronic media, such as the internet. Payments for E-commerce transactions appear in various forms, for example, e-wallet, micropayment, credit card, even with a cash on delivery (COD) payment system.Purposes of the Research: This research aims to understand and explain the regulations of cash on delivery payment systems in e-commerce and the legal consequences of product returns for business entities regarding cash on delivery payment systems. Methods of the Research: This is conducted through a normative legal method using a statutory approach and a conceptual approach.Findings of the Research: Based on this research, the regulation of the on-site payment system is regulated in the Civil Code, Consumer Protection Act, Electronic Information and Transaction Law and Government Regulation on the Implementation of Electronic Systems and Transactions. The legal consequences experienced by business entities regarding the return of goods made by consumers when shopping through E-commerce are paying compensation to consumers if the goods are not in accordance or damaged and returns with a mechanism that has been determined by each marketplace. The form of guarantee given by the marketplace if the goods are not in accordance or damaged is in the form of free shipping when returning goods which will be fully borne by the marketplace. Meanwhile, if the goods are in accordance, consumers cannot claim a guarantee and are required to make payments with the on-site payment system.